Current Management of Patients With Diverticulosis and Diverticular Disease: A Survey From the 2nd International Symposium on Diverticular Disease. (October 2016) - Tursi, Antonio; Picchio, Marcello; Elisei, Walter; Di Mario, Francesco; Scarpignato, Carmelo; Brandimarte, Giovanni
Abstract : Background: Management of diverticular disease (DD) remains a point of debate. Goals: To investigate the current opinion of participants of the 2nd International Symposium on Diverticular Disease, on real-life management of patients with DD of the colon. Study: Twelve questions were aimed at the diagnosis, treatment, and management options for diverticulosis and symptomatic DD. Results: In total, 115 surveys from 8 European Countries were filled out. High fiber diet was widely prescribed in diverticulosis (59.1%). Probiotics (25%) were the most frequent prescribed drug, whereas 29.8% of participants did not prescribe any treatment in diverticulosis. Colonoscopy was frequently prescribed in symptomatic patients (69.3%), whereas 72.9% of participants did not prescribe any instrumental tool in their follow-up. Rifaximin, probiotics, and mesalazine were the most frequent prescribed drugs both in symptomatic patients (28.1, 14.9%, and 11.4%, respectively) and to prevent recurrence of the disease (42.5%, 12.4%, and 28.2%, respectively). With respect to laboratory exams, 57.9% of participants prescribed them during follow-up. The majority of participants (64.9%) managed suspected acute diverticulitis at home. Rifaximin, probiotics, and mesalazine were the most frequent prescribed drugs to prevent recurrence of the disease (32.2%, 13.2%, and 11.4%, respectively), whereas 25.4% of participants did not prescribe any drugs. Finally, no differences were found among gastroenterologists, surgeons, and general practitioners in managing this disease. Conclusions: This surveys shows that current management of DD is similar between different medical specialities, generally in line with current literature.